Poor whites and the post-apartheid labour market: a study of perceptions and experiences of work among residents in a homeless shelter in Johannesburg - Wollnik, Nadjeschda (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
Despite historical precedents, poverty among white people in South Africa remains an anomaly and a paradox. Likewise, the perceptions of work and employment among poor (under- and unemployed) whites in contemporary South Africa have received scant attention in the scholarly literature. Using the conceptual frameworks of critical whiteness studies and segmented labour market theory "“ as a way of combining subjective and objective considerations "“ this research seeks to describe and explain the perceptions and experiences of the labour market among poor whites living in a homeless shelter in Johannesburg. Eight respondents were chosen for extended, in-depth interviews in an effort to develop a fine-grained understanding of the pre-existing circumstances that affected their access to information and thus shaped their choices in the labour market, as well as to ascertain what they believed to be the barriers that they face in the labour market. The findings varied, with most of the interviewees seeing 'being white' as the reason for their poverty and unemployment, while others exhibited some awareness of the role of their lack of skills and qualifications in their capacity to compete in higher segments of the labour market. The findings were also varied in the sense that not all interviewees experienced poverty in the same manner, with some having been part of the middle class prior to becoming poor, while others having been poor their entire lives. It was also found that class or socio-economic status seemed to have a greater impact than race on the labour market prospects of the interviewees. It is argued that the perceptions of these poor whites, which are informed by their lack of information about the workings of the labour market, rather than their lack of qualifications or their race, most affected their prospects in the labour market. The mechanisms they rely on when seeking employment reveal a poor knowledge of the local labour market and the ways in which they think their skillsets match up to the types of jobs they desire. The lack of understanding of the South African labour market and the policies that are in place to redress the legacies of apartheid are among the factors influencing the lack of success these poor whites are experiencing in their search for work.
Keywords: Poor whites -- South Africa; Poor whites -- South Africa -- Atitudes; Shelters for the homeless -- South Africa; Unemployed -- South Africa -- Attitudes; Unemployed -- South Africa; South Africa -- Social conditions -- 1994-; South Africa -- Economic conditions -- 1991-